INCREASING THE VALUE OF SOCIAL AND ABILITY OF THE CONCEPT OF UNDERSTANDING WITH MEDIA MULTICULTURAL EDUCATION MINDSCAPE AND COOPERATIVE LEARNING - Kirana Prama Dewi (Universitas Ahmad Dahlan, 2015)
The purpose of this classroom action research was to improve social values and through mindscape media and cooperative learning. The research subjects were students of class C PGSD UAD, in the academic year of 2013/2014. The results of the study showed that students social values and multicultural education materials concept understanding improved after the implementation of learning actions through mindscape media and cooperative learning in three segments.